Regulation of a plant aquaporin by a Casparian strip membrane domain protein‐like. (22nd March 2019) - Champeyroux, Chloé; Bellati, Jorge; Barberon, Marie; Rofidal, Valérie; Maurel, Christophe; Santoni, Véronique
Abstract: The absorption of soil water by roots allows plants to maintain their water status. At the endodermis, water transport can be affected by initial formation of a Casparian strip and further deposition of suberin lamellas and regulated by the function of aquaporins. Four Casparian strip membrane domain protein‐like (CASPL; CASPL1B1, CASPL1B2, CASPL1D1, and CASPL1D2) were previously shown to interact with PIP2;1. The present work shows that CASPL1B1, CASPL1B2, and CASPL1D2 are exclusively expressed in suberized endodermal cells, suggesting a cell‐specific role in suberization and/or water transport regulation. When compared with wild‐type plants, and by contrast to caspl1b1*caspl1b2 double loss of function, caspl1d1*caspl1d2 double mutants showed, in some control or NaCl stress experiments and not upon abscisic acid (ABA) treatment, a weak enlargement of the continuous suberization zone. None of the mutants showed root hydraulic conductivity ( L pr ) phenotype, whether in control, NaCl, or ABA treatment conditions. The data suggest a slight negative role for CASPL1D1 and CASPL1D2 in suberization under control or salt stress conditions, with no major impact on whole root transport functions. At the molecular level, CASPL1B1 was able to physically interact with PIP2;1 and potentially could influence the regulation of aquaporins by acting on their phosphorylated form. Abstract : At the endodermis, water transport can be affected by initial formation of a Casparian strip and further deposition of suberin lamellas and regulated by the function of aquaporins. Four Casparian strip membrane domain protein‐like (CASPL; CASPL1B1, CASPL1B2, CASPL1D1, and CASPL1D2) were recently shown to interact with PIP2;1. The present work shows an exclusive expression of CASPL1B1, CASPL1B2 and CASPL1D2 in suberized endodermal cells and describes a slight negative role for CASPL1D1 and CASPL1D2 in suberization under control or salt stress conditions, with no major impact on whole root transport functions. At the molecular level, CASPL1B1 was able to physically interact with PIP2;1 and potentially could influence the regulation of aquaporins by acting on their phosphorylated form.